Glycemic Profile and Clinical Treatment in Patients with Diabetes Mellitus-Tuberculosis: An Update Scoping Review - Rissaadah S; Nursiswati N; Pahria T (Journal of Multidisciplinary Healthcare)
Siti Rissaadah,1 Nursiswati Nursiswati,2 Tuti Pahria2 1Master of Nursing Study Program, Faculty of Nursing, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 2Department of Medical-Surgical Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, 45363, IndonesiaCorrespondence: Nursiswati Nursiswati, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Bandung Sumedang KM.21 Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +62895604502223, Email nursiswati@unpad.ac.idBackground: Type 2 diabetes mellitus (T2DM), characterized by chronic hyperglycemia, leads to a decreased immune system and increased susceptibility to infections, such as tuberculosis (TB). However, there are gaps in comprehensive reviews on the relationship between TB and the severity of glycemic control in patients with T2DM, characteristics of glycemic levels, and clinical treatment among patients with DM-TB.Purpose: The primary aim of this study is to explore the association of DM-TB and glycemic control. The secondary aim of this study was to explore the association between DM-TB, successful treatment, and TB severity.Methods: This study used a scoping review following the Arksey and O’Malley framework to provide an overview of glycemic control and clinical treatment of DM-TB. A literature search was performed using three databases, PubMed, Scopus, and Medline, with inclusion criteria for the population of patients with diabetes mellitus and tuberculosis who discuss glycemic control and clinical treatment. Critical appraisal in this study was assessed using the Joanna-Briggs Institute (JBI) critical appraisal tools.Results: We included 16 studies from a total of 741 articles in the initial search. The results of this study showed that patients with DM-TB were more likely to have poor glycemic control than those with diabetes mellitus (DM) without TB. Severe hyperglycemia in patients with DM-TB is associated with an increased risk of TB treatment failure, a long recovery time, and the likelihood of developing multi-drug-resistant tuberculosis (MDR-TB). In addition, patients with DM-TB who did not start TB treatment were more likely to have poorer glycemic control than patients with DM-TB who underwent active TB treatment.Conclusion: Patients with DM-TB, such as MDR-TB, are at a higher risk of poor glycemic control, treatment failure, and clinical severity. Adequate treatment, such as a continuum of glycemic monitoring and early detection and intervention for TB, is needed to improve treatment outcomes.Keywords: diabetes mellitus, DM-TB, glycemic control, tuberculosis